Is Mental Toughness Related with Motor Learning in Wrestling? - Ranjbar, Sadegh; Akbarnejad, Ali; Alizadeh, Ashkan; Fadakar, Ali (International Journal of Sport Studies for Health, 2023)
Background: In sport context learning a skill, and performing it flawlessly is of great importance. There is a unanimous consensus among sport scientists, coaches, and athletes, that along with physical, technical and tactical skills, psychological skills are also necessary for an optimal sport performance.Objectives: The aim of the present study was to investigate the role of mental toughness in motor learning and sport performance in wrestling.Methods: This study was semi-experimental and its population were physical education students of the University of Tehran in 2018. Using intensive sampling method, 28 student-athletes, who never had any past wrestling skill practices, were selected. Subsequently, using Mental Toughness-48 questionnaires, they were divided into two equal groups of high and low in mental toughness. After that, all participants were randomly assigned into two groups of equal size and 30 wrestling skills were taught to them twice a week for 3 months by two professional wrestling coaches. Their motor learning was assessed by three other professional coaches in the last week of training and one week after the last session. Motor learning score was obtained by calculating the mean scores of acquisition and retention stages. Then, two groups with high and low levels of mental toughness were compared regarding their motor learning scores. Tools used in this study included demographic consent form, wrestling skills test and The Mental Toughness Questionnaire-48 (MTQ 48).Results: The results suggested that mentally tough student-athletes demonstrated significantly higher motor learning scores compared with their counterparts who had lower levels of mental toughness (P ≤ 0/05). This advantage was persistent both in the acquisition and retention stages (P ≤ 0/05).Conclusions: It was concluded that mental toughness could be considered as a key factor in motor learning. Therefore, it is recommended to coaches and athletes to develop mental toughness in order to enhance motor learning and achieve successful performance.